Hydrogel implants for transscleral drug delivery for retinoblastoma treatment - Cocarta, Ana-Irina; Hobzová, Radka; Cerna, Tereza; Hrabeta, Jan; Svojgr, Karel; Pochop, Pavel; Kodetová, Martina; Jedelska, Jarmila; Bakowsky, Udo; Uhlik, Jiri; Sirc, Jakub (Materials science & engineering. C, Materials for biological applications, 2019)
Retinoblastoma (Rb) is the most common primary malignant intraocular tumor in children which develops from the retinal stem cells. Systemic chemotherapy is the typical therapeutic treatment and though most children survive Rb, they often lose their vision, or the eye needs to be enucleated. Regarding to the pure availability of the target tumor by systemic chemotherapy, the local anticancer drug administration would be advantageous to increase the local drug concentration and minimize adverse side effects of chemotherapy. The present paper describes a new hydrogel implant enabled to deliver therapeutically active doses of low molecular weight hydrophilic antitumor drugs topotecan and vincristine. The hydrogel implant is proposed as bi-layered with an inner hydrophilic layer from 2-hydroxyethyl methacrylate (HEMA) serving as a reservoir of the chemotherapeutic agent and an outer hydrophobic layer from 2-ethoxyethyl methacrylate (EOEMA) acting as a barrier to protect the surrounding vascularized tissue against cytotoxicity of the delivered chemotherapeutics. The experiments with enucleated pig eyes demonstrated the ability of tested drugs to diffuse through sclera and reach the vitreous humor. HEMA-based hydrogels were examined in terms of sorption, release and transport properties, showing the possibility of adjusting the loading capacity and diffusion of the drugs by the degree of crosslinking. The EOEMA-based gels proved to be an inert for drug sorption and diffusion. A chorioallantoic membrane assay demonstrated excellent biocompatibility of unloaded hydrogels, and in vitro experiments confirmed significant cytotoxicity of drug-loaded hydrogels against a Rb cell line; 2 days for those topotecan-loaded and a minimum of 6 days for vincristine-loaded hydrogels. The bi-layered hydrogel implant can be considered promising for local administration of active agents to eye-globe for the treatment of Rb and also other ocular disorders.
Keywords: prasata; topotekan; Swine; viabilita buněk; protézy a implantáty; Cell Line, Tumor; Eye; vysokoúčinná kapalinová chromatografie; Hydrogels; retinoblastom; Cell Survival; Vincristine; methakryláty; Drug Carriers; Drug Stability; hydrogely; Topotecan; Chromatography, High Pressure Liquid; kinetika; Animals; lidé; stabilita léku; oči; Humans; Retinoblastoma; zvířata; Prostheses and Implants; nádorové buněčné linie; nosiče léků; Methacrylates; Kinetics; vinkristin